The awareness of Kadazandusun's student in SMK St. Micheal towards Kadazandusun language: an observation in Penampang Sabah / Evainesta Albert and Judith Leku Lisa @ Donney - Albert, Evainesta; Leku Lisa @ Donney, Judith (2015)
Sabah is known for her diversity in terms of the ethnicities and cultures. Among one of the largest ethnic in Sabah is the Kadazandusun. However, the usage of the Kadazandusun language seems declining among the youth. This study aims to determine the level of awareness among the Kadazandusun students towards their Kadazandusun dialects. It also investigates the relationships between the factors and level of students' awareness towards the Kadazandusun language. This study was quantitative in nature and a total of 123 respondents were randomly selected in SMK St Micheal, Penampang. The findings revealed that the level of the awareness among of the KD students correlated with the variables. It also found that the level of awareness of KD students towards KD language was high. The factors such as families, Government. NGO's, and the media that influenced had a significant relationship between their level of awareness and the usage of Kadazandusun dialects. Thus, it is suggested that the school has to enhance the KD language through introducing KD Language Day in corresponding to preserve the KD language.